Beltanelliformis konovalovi sp. nov. From the Terminal Neoproterozoic of Central Urals: Taphonomic and Ecological Implications - Kolesnikov, Anton (Frontiers in Earth Science, 2022)
The siliciclastic succession of the Ediacaran Chernyi Kamen Formation in Central Urals of Russia contains rich complex of Ediacaran fossils that represents in situ benthic populations buried in life position. The present work reports Beltanelliformis konovalovi sp. nov. found as palaeocommunity of organisms and studied for their morphology and spatial distribution. Unlike the type species (B. brunsae), new fossil is preserved within fine-grained sandstone beds as three-dimensional pancake-like or flattened discoidal single, paired or occasionally aggregated bodies with ultra-thin rim. Statistical analysis shows a significant predominance of small individuals in the palaeocommunity, which in turn manifest different spatial distribution in comparison with larger ones. In addition, the studied palaeocommunity exhibits patterns of self-organisation in extremely shallow marine environment and adaption to periodic desiccation. These results provide quantitative support for the more complex ecology of Beltanelliformis and also expand the range of taphonomic possibilities of macroscopic life in terminal Neoproterozoic.